Hygrothermolytic wood modification. process description and treatment level characterisation. Issue 4 (3rd July 2020) - Willems, W.; Altgen, M.
ABSTRACT: This article describes and explains a relatively unknown thermal wood modification process in pressurised unsaturated steam. Compared to other processes for the thermal conversion of wood, this hygrothermolytic (HGT) process has the unique feature of an additional independent and continuous process variable, enabling the full control of the water activity throughout the entire heating cycle. This process covers the technology gap between dry thermal and hydrothermal processes, offering a potential to optimise between the extreme processes, in search for improved material properties and improved process characteristics. The suitability of four different treatment intensity markers (mass loss, equilibrium moisture content, oxygen/carbon (O/C) atomic ratio and electron spin resonance signal) is tested on beech wood over the entire range from low-pressure (dry) to high-pressure (moist and wet) processes. Each marker has its own merits and different sensitivity for the broad palette of changing physicochemical wood properties during heat treatment, but all methods proved to be useful for routine production quality control. The O/C-ratio has the unique advantage that it provides an absolute thermal treatment level rating, neither requiring a control reference nor the knowledge of the wood species and any of the thermal treatment process details.